2019
DOI: 10.1007/s12034-019-1981-3
|View full text |Cite
|
Sign up to set email alerts
|

Candle soot-coated egg carton material for oil water separation and detergent adsorption

Abstract: A hydrophobic and superoleophilic adsorbent was prepared by coating candle soot (CS) on the surface of a recycled egg carton material (ECM). This waste material has been explored as a cost-effective adsorbent to remove oil and detergent from water. The surface of the material was coated with CS solution prepared by mixing soot with acetone and characterized by scanning electron microscopy and contact angle measurements. The rate of fall of contact angle for water and oil was evident of water rejection and oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This indicates the excellent reusability and durability of the aerogel for oil-water separation applications. Azad et al developed a hydrophobic and superoleophilic adsorbent by applying a coating of candle soot onto the surface of a recycled egg carton material [40]. The resultant carbon-coated adsorbent demonstrated an exceptional oil absorption capacity across a wide range of densities, eliminating the necessity for pre-treatments or surface modifications.…”
Section: Adsorptionmentioning
confidence: 99%
“…This indicates the excellent reusability and durability of the aerogel for oil-water separation applications. Azad et al developed a hydrophobic and superoleophilic adsorbent by applying a coating of candle soot onto the surface of a recycled egg carton material [40]. The resultant carbon-coated adsorbent demonstrated an exceptional oil absorption capacity across a wide range of densities, eliminating the necessity for pre-treatments or surface modifications.…”
Section: Adsorptionmentioning
confidence: 99%
“…Keeping this in view, Azad et al coated CS on the surface of an egg carton material (ECM), which showed hydrophobic properties and was used for oil−water separation by adsorbing different types of oils and detergents from the mixture, as shown in Figure 10A. 148 Gunture et al isolated ONCs from hazardous DS, oxidized them to make them water-soluble, used them for the adsorption of three model anionic dyes as methylene blue (MB), crystal violet (CV), and rhodamine B (RhB) (Figure 10B,C), 73 and found the maximum adsorption toward MB from the three tested dyes. Mishra et al used a poly(vinylidene fluoride)−cam-soot composite for the oil−water separation and showed the excellent reusability of the material for the same process, as shown in Figure 10D,E.…”
Section: Applications Of Pollutant-soot-derived Nanocarbonmentioning
confidence: 99%
“…This adsorption approach via BC-derived nanocarbons is quite impressive and easier. Keeping this in view, Azad et al coated CS on the surface of an egg carton material (ECM), which showed hydrophobic properties and was used for oil–water separation by adsorbing different types of oils and detergents from the mixture, as shown in Figure A . Gunture et al isolated ONCs from hazardous DS, oxidized them to make them water-soluble, used them for the adsorption of three model anionic dyes as methylene blue (MB), crystal violet (CV), and rhodamine B (RhB) (Figure B,C), and found the maximum adsorption toward MB from the three tested dyes.…”
Section: Applications Of Pollutant-soot-derived Nanocarbonmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these materials have not been evaluated as oil/water separation absorbents. The soot‐embedded polyvinylidene fluoride (PVDF) nanofibrous membrane, [ 47 ] CS‐coated nickel foam, [ 48 ] copper mesh, [ 10 ] melamine sponge, [ 49 ] and egg carton materials [ 50 ] are examples. However, CS particles have fragile adhesion to substrate materials in most cases, which must be addressed to make them robust and reusable for oil/water separation.…”
Section: Introductionmentioning
confidence: 99%